Determination of heat flux layout in the mould for continuous casting of steel - R. Pyszko (Metalurgija, 2012)
The paper deals with research of the heat transfer in the mould of continuous casting and the thermal boundary condition determination using combination of measurement and the inverse technique of numerical simulation. An average heat flux in the mould is calculated from measured parameters of mould cooling water. Layout of the heat flux at the mould working surface is derived by the original experimental and numerical simulation procedure, which is based on measuring temperatures in the mould walls and solving a numerical inverse problem including stress and shrinkage, using the software package Procast. A database of the heat flux layouts was built for various values of casting speed and steel chemical composition for purpose of determination the boundary condition for on-line modeling.